The seed bank of a gallery forest in Southeastern Brazil - Grombone-Guaratini,Maria Tereza (2004)
The soil seed bank was studied in a gallery forest in Southeastern Brazil. Samples were collected from edge to edge along transects perpendicular to the river during the wet (December, 1990) and dry (August, 1991) seasons. The number of seeds found in the seed bank samples was greater in the dry season than in the wet season indicating that there was important variation in the seed stocks in these two periods. The similarity values between the seed bank and the community composition were low. The high density of weed species might be reflecting forest fragmentation and indicating a degree of perturbation.